The Role of the Private Sector in Lagos, Nigeria - Abdul-Hamid, Husein; Baum, Donald; Lusk-Stover, Oni; Wesley, Hugo (World Bank, Washington, DC, 2017)
Private schools are currently educating the majority of primary and secondary education students in Lagos State, Nigeria. As such, Lagos is one of the largest private school markets in the world. Notwithstanding the influence of this sector, not enough is known about the operations of private schools in Lagos State, their impact on student learning opportunities, and their overall implications for the economic and social development of Nigeria. This report presents results from analyses of: (i) the regulatory environment governing private education provision; (ii) implementation of existing regulations; and (iii) the provision of private school services in Lagos. The results of this research can be used to inform the government on how to effectively regulate and engage with the private education sector.